2010
DOI: 10.1021/jp909122x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Energetic Determinants of Thermal Stability and Hierarchical Unfolding Pathways of Hyperthermophilic Proteins, Sac7d and Sso7d

Abstract: Identification of the structural and energetic determinants responsible for enhancing the stability of proteins is crucial. Hyperthermophilic proteins are naturally occurring proteins that exhibit high thermal stability and are good candidates for the investigation and understanding of structure-stability relationships. Sac7d from Sulfolobus acidocaldarius and Sso7d from Sulfolobus solfactaricus are two homologous hyperthermophilic proteins that were shown to be quite stable at high temperatures. Molecular dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Several positively charged, surface residues at the interface rim form salt bridges with DNA and are involved in stabilizing the protein fold . Sac7d–DNA complexes are also stable during MD simulations at high temperatures (360 K) . Simulations on the Sac7d–DNA also indicate that partial DNA bending can occur even without residue intercalation at the target site .…”
Section: Figurementioning
confidence: 99%
“…Several positively charged, surface residues at the interface rim form salt bridges with DNA and are involved in stabilizing the protein fold . Sac7d–DNA complexes are also stable during MD simulations at high temperatures (360 K) . Simulations on the Sac7d–DNA also indicate that partial DNA bending can occur even without residue intercalation at the target site .…”
Section: Figurementioning
confidence: 99%
“…[3,[45][46][47][48][49] There are numerous charged residues in Ssh10b, and they form salt bridges in each monomer, such as Glu36/Lys68, Glu54/Arg57, Asp63/Lys97, and Glu66/Arg95. The previous analysis found that the salt bridges of Ssh10b seems to be crucial in maintaining the 3D structures at elevated temperatures.…”
Section: Salt Bridge Networkmentioning
confidence: 99%
“…The previous analysis found that the salt bridges of Ssh10b seems to be crucial in maintaining the 3D structures at elevated temperatures. [49] Except for the salt bridges mentioned above in each monomer, we also monitored some salt bridges between monomer and monomer, such as Asp51/Arg86, Glu91/Arg71, Glu69/Arg71, Glu54/Arg86, Glu69/Arg95, and Glu91/Lys40 (Supporting Information Table S6). The salt bridges distributed in sheet-sheet, intrahelix and helix-sheet.…”
Section: Salt Bridge Networkmentioning
confidence: 99%
“…21,41,45,46 Briefly, the systems were subjected to a 500-step steepest decent (SD) minimization with harmonic restraints on heavy atoms of the protein and DNA-RNA hybrid together with the crystal Mg 2+ and water molecules. These minimized systems were then immersed in a pre-equilibrated water box and were made electrically neutral by adding sufficient number of ions.…”
Section: Simulation Protocolmentioning
confidence: 99%